ANALISIS PENGGUNAAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (KHANZA) DENGAN METODE EUCS DI BAGIAN PENDAFTARAN RUMAH SAKIT X TAHUN 2025 - Azlina Azlina; Tri Purnama Sari; Siti Hasanah; Wen Via Trisna; Novia Andriyani (LPPM Universitas Awal Bros, 2026)
The implementation of Hospital Management Information Systems (HMIS) plays an important role in improving the efficiency and quality of healthcare services. However, evaluations of end-user satisfaction, particularly among registration officers, remain limited. This study aimed to analyze user satisfaction with the KHANZA HMIS at the Registration Unit of Hospital X using the End User Computing Satisfaction (EUCS) method. A descriptive qualitative approach was employed involving four registration officers and one head of the registration unit as informants. Data were collected through in-depth interviews, observations, and document review, then analyzed using qualitative content analysis based on five EUCS dimensions: content, accuracy, format, ease of use, and timeliness. The findings revealed that KHANZA was generally perceived positively by users. Ease of use emerged as the strongest dimension due to regular training and system familiarity. Content and accuracy dimensions were considered adequate in supporting registration activities, although limitations were identified in patient history summaries and data correction processes. Meanwhile, format and timeliness dimensions still require improvement, particularly regarding interface design and system response time during peak service hours. The study concludes that KHANZA effectively supports registration services; however, interface enhancement, infrastructure optimization, and improved information retrieval features are needed to increase overall user satisfaction.